2017
DOI: 10.1177/0033354917739581
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of a Community’s Health Needs and Nonprofit Hospitals’ Progress in Meeting Those Needs: Are We Faced With a Paradox?

Abstract: Hospitals serving communities with the greatest health needs face high demand for free and reduced-cost care, which may limit their ability to invest more of their community benefit dollars in initiatives aimed at improving the health of the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Another did not investigate vulnerable populations but the most vulnerable communities. Singh, Cramer, and Young found that hospitals in communities with the lowest health needs based on County Health Rankings were more likely to have completed CHNA activities than hospitals in communities with the greatest health needs (59). For those interested in community benefit as a mechanism for addressing inequity, this data point could be concerning.…”
Section: Community Assessment: Processmentioning
confidence: 99%
“…Another did not investigate vulnerable populations but the most vulnerable communities. Singh, Cramer, and Young found that hospitals in communities with the lowest health needs based on County Health Rankings were more likely to have completed CHNA activities than hospitals in communities with the greatest health needs (59). For those interested in community benefit as a mechanism for addressing inequity, this data point could be concerning.…”
Section: Community Assessment: Processmentioning
confidence: 99%
“…Research shows that social capital—the networks and shared values that reflect community level trust needed to pursue shared objectives—is key to understanding and shaping change efforts ( Putnam, 1995 , 2002 ). Although engaging hospitals to participate in broader public health networks is critical, there is still considerable variation in the number of hospitals who are partnering with public health and community organizations and in the types of relationships developed to improve health outcomes and reduce health disparities ( Hogg & Varda, 2016 ; Singh, Cramer, & Young, 2018 ). This paper examines hospitals’ decisions to partner with public health and other community organizations using the theoretical framework of social capital.…”
Section: Introductionmentioning
confidence: 99%
“…This study excludes public hospitals because they usually reside inherently in a different context from their counterparts [42]. Many public hospitals primarily serve special groups, such as Native Americans, military personnel, and veterans, not the general public.…”
Section: Sample and Data Sourcesmentioning
confidence: 99%